The interchangeability of original tumor necrosis factor- α inhibitors and biosimilars in rheumatology: experience in replacing original infliximab with Flammagis for ankylosing spondylitis - Yu. V. Muravyev; V. V. Lebedeva; A. S. Starkova; D. G. Rumyantseva; M. M. Urumova; Sh. Erdes (Современная ревматология)
The paper discusses prospects for prescribing tumor necrosis factor-α (TNF-α) inhibitor biosimilars, their interchangeability with original drugs for inflammatory joint diseases. It describes clinical cases when original infliximab is replaced with its biosimilar Flammagis for ankylosing spondylitis. The authors emphasize that it is difficult to predict the interchangeability of original TNF-α inhibitors and biosimilars in rheumatology, and this is confirmed by the above clinical cases. They also indicate that the optimal use of biosimilars requires a constant cooperation of rheumatologists, pharmacologists, and regulatory authorities, which is aimed at protecting the rights of a patient in order to ensure safe, effective and high-quality care. It is concluded that it is advisable to conduct further investigations to develop a special pharmacovigilance system in this area.